Analisis Kinerja Keuangan Sektor Farmasi Yang Terdaftar Di BEI Sebelum Dan Saat Covid-19 - Firdausi Nuzula, Salsabila; Siregar, Cantika Sari (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Financial performance is a reference that the company wants to achieve in the future within a certain period of time, which effectively and efficiently reflects the health of the company. This study aims to obtain information on the financial performance of pharmaceutical sector companies listed on the IDX before and during COVID-19. The research method used in this research is descriptive quantitative. The data analysis technique used is the profitability ratio with secondary data collection. The results of the analysis show that COVID-19 affects the financial performance of pharmaceutical sector companies listed on the Indonesia Stock Exchange. There are several companies experiencing an increase in profitability ratios before and during COVID-19, but not significantly. This supports the agency theory and the signal theory that management has managed the company effectively so that there is an increase in profits. A high profitability ratio is a good signal for investors to invest their shares in the company so that the value of the company's shares will rise.